Visible-light enhanced photocatalytic performance of polypyrrole/g-C3N4 composites for water splitting to evolve H2 and pollutants degradation - Hayat, Asif; Raziq, Fazal; Khan, Muhammad; Ullah, Ikram; Ur Rahman, Mati; Khan, Wasim Ullah; Khan, Javid; Ahmad, Akhlaq (Journal of photochemistry and photobiology. A, Chemistry., 2019)
[Display omitted] •Conducting polypyrrole (PPy) nanoparticles was fabricated into the skeleton of inorganic semi-conductor g-C3N4 by loading of its small amount and processed for the evolution of hydrogen energy from water splitting and also demonstrated these fabricated composites for the photo-degradation phenomena under visible light illumination (λ = 420 nm).•The installment of small amount of PPy in the co-ordination of g-C3N4 consequently prolonging the specific surface area, fasten the charge carrier separation, improve the photo-generating electron-hole separation, explore optical absorbance and its exclusive influence on the morphology, structures, optical absorption properties and emission features of the whole skeleton of g-C3N4.•Interestingly this perspective junction of PPy/ g-C3N4 thus hindering the conductivity of photo-generated electrons and transfer to the conduction band (CB) of g-C3N4 to oxidize the water to hydrogen peroxide (H2O2) and finally reduced the water to hydrogen (photo-reduction) due to more negativity of conduction band (CB) of PPy as compared to g-C3N4 and hence facilitate in the production level of hydrogen energy.•For instance, the aforementioned pretreatment of polypyrrole (PPy) convoluted in the framework of g-C3N4 also depicting a synergistic activity in the photocatalytic performance of the degradation of RhB and 2,4-dichlorophenol (2,4-DCP) degradation with high stability under visible light illumination 420 nm respectively. In this work, we report the fabrication of polypyrrole/g-C3N4 (PPy/g-C3N4) nanocomposites via simple wet-chemical method. The photocatalytic activities of the composites are evaluated for water splitting to evolve H2, Rhodamine B dye (RhB) and 2,4-dichlorophenol (2,4-DCP) degradation under visible-light. The results reveal that the photocatalytic performance of g-C3N4 for H2 evolution, RhB dye and 2, 4-DCP degradation are significantly improved after coupling polypyrrole (PPy). Worth noting, the amount optimized (1 wt%PPy/g-C3N4) photocatalyst showed highest photoactivity compared to the other photocatalysts. Further, it is confirmed by means of radical trapping experiments that superoxide radical (O2−) is the dominant specie involved in the degradation of pollutants over PPy/g-C3N4 nano-composites. Moreover, clear photocatalytic reactions for H2 evolution and pollutants degradation are proposed. This work would help us to deeply understand the reaction mechanism and will provide feasible routes to fabricate g-C3N4 based highly efficient photocatalysts for energy and environmental applications.